Peran Sekretariat Dewan Perwakilan Rakyat Daerah Dalam Membantu Pelaksanaan Administrasi Fungsi Dewan Perwakilan Rakyat Daerah Provinsi Jawa Timur - Bayu Satrio Nugroho (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The existence of the DPRD Secretariat is an inseparable part of the government structure, both at the provincial and district/city levels, and is closely related to the performance of the DPRD. However, many parties still do not understand the role and function of the DPRD Secretariat (Setwan) in its daily activities. Therefore, this study aims to analyze the role of the DPRD Secretariat in supporting the implementation of the DPRD's administrative functions at the provincial level. This study uses a qualitative descriptive approach with the research location at the East Java Provincial DPRD Secretariat Office. The research informants consisted of 11 people including DPRD members, officials, and staff within the East Java Provincial DPRD. The data analysis technique was carried out using the triangulation method, namely matching data from interviews, observations, and supporting documents or other opinions. The results of the study indicate that in the implementation of the representative function of the Provincial DPRD, the role of the Secretariat of the East Java Provincial DPRD, especially the staff, is still limited to facilitating the needs of completeness to support the three functions of the DPRD. The DPRD Secretary who comes from the Civil Servant (PNS) and is tasked with serving the Provincial People's Representative Council, as well as the needs of the DPRD, has played a role but has not been fully optimal. Overall, although the staff only plays a role in facilitating the needs of the DPRD, performance improvements are needed so that they can be more careful in preparing all the needs of DPRD Members, especially in supporting the legislative function. In addition, it is recommended that staff participate in education and training programs more often to improve their competence. The factors that hinder the Secretariat of the East Java Provincial DPRD in supporting the functions of the DPRD include the existence of excessive division of labor or specialization within the organization and the lack of staff ability to carry out coordination effectively.